2010
DOI: 10.1007/s11390-010-9386-1
|View full text |Cite
|
Sign up to set email alerts
|

A Generalization of Haussler's Convolution Kernel — Mapping Kernel and Its Application to Tree Kernels

Abstract: Haussler's convolution kernel provides an effective framework for engineering positive semidefinite kernels, and has a wide range of applications. On the other hand, the mapping kernel that we introduce in this paper is its natural generalization, and will enlarge the range of application significantly. Our main theorem with respect to positive semidefiniteness of the mapping kernel (1) implies Haussler's theorem as a corollary, (2) exhibits an easy-to-check necessary and sufficient condition for mapping kerne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…In this paper new kernel functions, based on the convolution kernel [37] and on mapping kernel template proposed by Shin et al ( [38]) are introduced for hierarchical control flow graphs.…”
Section: B Kernel Methods For Programsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper new kernel functions, based on the convolution kernel [37] and on mapping kernel template proposed by Shin et al ( [38]) are introduced for hierarchical control flow graphs.…”
Section: B Kernel Methods For Programsmentioning
confidence: 99%
“…The main idea of these kernels is to use the number of substructures of any structured object. This approach was extended by Shin et al [38], who proposed a mapping kernel for tree data.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Haussler's convolution kernel ( [2]) is an effective tool to design positive definite kernels. Recently, Shin et al ( [3]) generalized Haussler's convolution kernel, and introduced the notion of mapping kernel. Moreover, they applied the framework of mapping kernel to tree structures, and revealed that 13 of 19 tree kernels known in the literature are defined according to the single template formula of…”
Section: Introductionmentioning
confidence: 99%
“…Shin and Kuboyama ( [3]) reported that 18 of 19 tree kernels known in the literature can be defined as mapping kernels, and in particular, 13 of 18 are of the form (5) for different M X,Y .…”
Section: Introductionmentioning
confidence: 99%